Diseño de un plan de desarrollo para la organización de la junta parroquial de Lloa, provincia de Pichincha periodo 2011 - 2015 - Tello Santillán, Jaime Enrique (2011)
This manual brings the identification of each of the charges set forth in the Vestry of Lloa, which has the designation lifting profiles. Lifting profiles detailing each of the posts, within which the level of education that the person must have the knowledge, the level of security risk and therefore, the main responsibilities and activities to exercise specified, facilitating this understanding of the worker and setting a target for each job. This implementation will prevent and discard the deficiencies that appeared in the daily lives of the Vestry having no regulation or manual to follow to avoid the constant failures in the labor system.